Numerical Analysis of Rapid Drawdown of an Embankment Dam - Bhutto, A. H.; Bhurgri, G. S.; Zardari, S.; Zardari, M. A.; Bhanbhro, R.; Memon, B. A. (Engineering, Technology & Applied Science Research, 2020)
Numerical analysis for the safe rate determination of lowering of an embankment dam was performed in this study with the use of the finite element method. Coupled deformation and consolidation analysis were carried out for staged construction and drawdown of a 59m embankment dam for varying undrained shear strength of the clay core. The lowering of the reservoir was performed at different depths between two extreme scenarios, i.e. rapid lowering rate (1m/day) and slow lowering rate (0.1m/day). The reservoir of the dam was lowered to a depth from 10m to 55m in gradual increments. The results indicated that the safety of the dam was satisfactory when the reservoir was lowered at the quick rate for a depth of 10m, 20m, 30m respectively when the undrained shear strength of the clay core was taken as 20, 25 and 30kN/m2. Regarding the case of slow drawdown rate of the reservoir, it was found that the reservoir could be lowered up to a depth of 55m at a rate of 0.1m/day when the undrained strength of clay core was 25kN/m2. The stability of the dam was also found satisfactory even though the reservoir was lowered at a rate of 0.25m/day for a depth of 55m when the undrained shear strength of clay core was 30kN/m2.